Disturbances of Temperature-Depth Profiles by Surface Warming and Groundwater Flow Convection in Kumamoto Plain, Japan - Linyao Dong; Congsheng Fu; Jigen Liu; Yifeng Wang (Geofluids)
Subsurface temperatures depend on climate and groundwater flow. A lack of observations of subsurface temperature collected over decades limits interpretation of the combined influences of surface warming and groundwater flow on subsurface thermal regimes. Subsurface temperature-depth profile data acquired for Kumamoto Plain, Japan, between 1987 and 2012 were collected and analyzed to elucidate regional groundwater and heat flows. The observed and simulated temperature-depth profiles showed the following: subsurface water flows from northeast to southwest in the study area; the combined influence of surface warming and water flow perturbation produces different temporal changes in thermal profiles in recharge, intermediate, and discharge areas; and aquifer thermal properties contribute more than hydraulic parameters to the perturbation of temperature-depth profiles. Spatial and temporal evolution features of subsurface thermal regimes may be utilized to investigate the influence of surface warming events on subsurface water and heat flows at the basin scale.